Thermal performance of axially restrained steel beams with slant end-plate connections - Zahmatkesh, Farshad (2015)
Steel beams restrained at their ends exhibit lower structural performance when subjected to thermally induce axial expansion. In this regard, the design of the connection plays an utmost essential role in restrained beams in order to dissipate the thermal force. Most existing studies on the thermal behaviour of connections have so far focused only on conventionally vertical end-plate type. This research describes mechanical behaviour of axially restrained steel beams with slant end-plate connection under thermal increase and gravity loads (symmetric and non-symmetric). The analytical, numerical and experimental approaches were used in this study. The analytical method was designed to simplify and simulate the proposed slant end-plate connections based on force equilibrium at the connection. The numerical approach was employed to expand the analytical simplified models by direct stiffness method and 3D finite element computer program (ABAQUS). As a verification, three specimens with different sizes and slanting angles were tested in the laboratory as well as studied using analytical and finite element models. The results of the analytical and numerical approaches as well as experimental tests proved that the slant end-plate connection can successfully reduce the extra thermal axial forces through small upward sliding at the end of the beam on the inclined end-plates. The results demonstrated that the steel beam with slant end-plate connections can reduce the thermal axial stress from 80% to 90% in comparison to the vertical end-plate connections. For the influence of pattern of loading it was concluded that the axial load-bearing of a steel beam under symmetric gravity load is higher than similar case under non-symmetric load at room temperature but, these values are the same at elevated temperature conditions. Based on the good agreement between theoretical and experimental methods, a series of design curves were developed as a safe practical range for the slant end-plate connections which depends on the geometrical and mechanical conditions of the connection.